A closed-form solution for the bending analysis of composite sandwich pipe with compliance core based on high-order sandwich theory. (September 2020) - Maleki, I; Rahmani, O
In this paper, bending of cylindrical sandwich pipes based on the high-order theory of sandwich structures with flexible core is investigated. The cylindrical sandwich pipe is composed of a flexible core and two composite face sheets. Behavior of the cylindrical sandwich pipe is described by a high-order sandwich shell theory, which explains nonlinear distortions of cross-sectional plane of the flexible core as well as changes in its height. The theory based on variational principles and using an extremely thorough systematic closed-form approach is formulated. In this model, no assumption has been considered for displacement distribution of core components. In this study, stress and displacement of the flexible core are obtained through a three-dimensional elasticity solution and the face sheets are modeled using classical shell theory. Also, a comparison is made in order to verify high-order solution results between a closed-form solution, which is expanded for simply supported boundary conditions and results that are obtained from the commercial finite element method. Finally, influences of physical and geometrical parameters on behavior of the cylindrical sandwich pipe are investigated.